Improving the quality of life of the people as a priority task of the Belarusian state - Babosov, Evgenii M. (Journal of the Belarusian State University. Sociology, 2025)
The features and significance of human potential, digitalisation and nanotechnology in modern society are studied. The transformations are analysed in the context of improving the quality of human life, which is a priority task of the Belarusian state. The quality of life is considered as a multicomponent, dynamically developing system of satisfaction of material, spiritual and social needs, the level of intellectual, cultural and physical development, as well as the degree of life security. Among the components of the quality of life the human potential is singled out, which is presented as an integral multicomponent phenomenon characterising the opportunities, desires, expectations and aspirations of the individual, fundamentally affecting his activity in various spheres of society. Human capital is considered as the most constructive and effective manifestation of human potential. Such trends characteristic of the first quarter of the 21st century as comprehensive digitalisation and the increasing role of artificial intelligence are highlighted. The social risks of the digital world are highlighted: digital dementia, escapism (escape from reality), manipulation of public consciousness, spiritual and moral degradation of the individual, one-sidedness and clipped thinking, crisis of rationality, cybercrime, the danger of total control over people. Among the most important areas of digitalisation of modern society is the formation of a digital state.